Balanceamento de chamadas VoIP a transcodificar - Cunha, Italo Tiago da (2009)
The present work relates to the VoIP (Voice over Internet Protocol) technology that uses the network protocol, IP (Internet Protocol) to provide communication through data networks, giving economy and mobility to the calls. In order to establish and manage call it is necessary the use a Session Server Module. For this, it is supposed that the participants have identical codecs as well there is a functionality responsible to transform an audio binary stream into another with the same property of initial information. However, in order to establish calls in case of distinct codecs it is necessary the transcoding operation, which consists in the conversion of an audio stream into another, which requires the use of Media Gateways, that are able to do this, but with considerable processor demand. This may become a problem when the number of simultaneous calls to be transcoded increases. Knowing this, the aim of this work is to provide the balancing of VoIP calls that need to be transcoded that is possible by means of developing a Call Balancing Module. This is an original solution that provides concrete results.